Operation of the aircraft as a discipline of knowledge after 100 years of experience - Stanisław Danilecki; Sławomir Tkaczuk (Biuletyn Wojskowej Akademii Technicznej, 2015)
The paper presents the course of the most important stages of development of the discipline related to the maintenance of aircrafts, as a synthesis of the 100-year experience. It is presented linking of technical maintenance of the aircraft with other disciplines of knowledge. The scope of technical maintenance was defined. The division and analysis of the methods for the maintenance was made. There were defined and discussed definitions used in the theory of maintenance, in conjunction with the construction of the aircraft and the tasks arising for constructor-manufacturer. MSG subsequent versions of the document constituting the logistical procedures for determining the programmable handling of civil airplanes were discussed.[b]Keywords[/b]: aviation, aircraft, maintenance aircrafts